Driving demands, stress reactivity and driving behavior: An interactional approach. (February 2020) - Tement, Sara; Plohl, Nejc; Horvat, Marina; Musil, Bojan; Jakus, Grega; Sodnik, Jaka
Highlights: Participants' driving performance generally improved in highly demanding scenarios. Information processing demands had a stronger impact than vehicle handling demands. Individuals' predisposition to emotional distress generally does not diminish their adaptive capability. Abstract: The aim of the present study was to investigate the role of driving demands, neuroticism, and their interaction when predicting driving behavior. More precisely, we strived to examine how driving behaviors (i.e., speeding, winding, tailgating and jerky driving) unfold across low and high driving demands and whether they are contingent on a personality factor that has previously been linked to stress reactivity. In a driving simulator, 50 participants with a valid driver's license (56.6% female, age: M  = 30.13, SD  = 10.16) were exposed to driving scenarios of different levels of information processing and vehicle handling demands. Additionally, they filled-out a self-report questionnaire that measured their neuroticism. We found that driving behavior became safer in scenarios that were highly demanding in terms of information processing, while this pattern did not emerge with vehicle handling demands. Moreover, tentative support was found for the notion that individuals high in neuroticism are less able to adapt their behavior to higher information processing demands. The present study offers new insights on driving demands in a simulated driving context and points to the potential importance of exploring interactions between personality and situational factors when understanding driving behavior. Additionally, the results of the present study may be used to adapt driver's education programs.